2005
DOI: 10.1136/bmj.38397.633588.8f
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of nurse led intermediate care versus standard care for post-acute medical patients: cost minimisation analysis of data from a randomised controlled trial

Abstract: Objective To undertake an economic evaluation of nurse led intermediate care compared with standard hospital care for post-acute medical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 7 publications
0
22
0
1
Order By: Relevance
“…The goal was to create a department functioning as a new link between advanced care at a general hospital and community home care to optimise recovery before returning home after general hospital care [7]. There is little published knowledge about patient outcome and cost effectiveness when intermediate care [9] is provided at a community hospital instead of standard care at a general hospital [10-14]. …”
Section: Introductionmentioning
confidence: 99%
“…The goal was to create a department functioning as a new link between advanced care at a general hospital and community home care to optimise recovery before returning home after general hospital care [7]. There is little published knowledge about patient outcome and cost effectiveness when intermediate care [9] is provided at a community hospital instead of standard care at a general hospital [10-14]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a financial analysis of this trial found significantly higher mean costs at six months in the nurse-led unit (mean excess £2,710 per patient, 95% CI £518 to £4,903). 31 A further similar trial randomised 175 patients (mean age 78.3 years) to a nurse-led unit or standard care. 32 Again, lengths of stay were longer in the intervention arm (mean excess stay 10.9 days, 95% CI 1.1-20.7 days), and costs were greater but this did not reach statistical significance (mean excess £1,044, 95% CI -£382 to £2,471).…”
Section: Nurse-led Unitsmentioning
confidence: 99%
“…However, this may not necessarily mean lower cost, particularly if undertaken within acute hospital environments. [9][10][11] There is often a high degree of substitution between these different forms of care, reflecting differences in clinical management of patients, in administrative processes including type-changing between different episodes of care and in the availability of appropriate treatment settings for each type of care, particularly in rural areas.…”
Section: Definition Of Subacute Carementioning
confidence: 99%